The Effect of Service Quality and Digital Access on Academic Service Satisfaction with Previous Experience as an Intervening Variable (Case Study at Bahaudin Mudhary University, Madura) - Rindya Ayu Nurviana; Rachmad Hidayat; Sri Rahayu; Rifda Fitrianty (Universitas KH. Abdul Chalim Mojokerto, 2026)
This study aims to analyze the influence of academic service quality and digital access on student academic service satisfaction with previous experience as an intervening variable at Bahaudin Mudhary University, Madura (UNIBA Madura). This study uses a quantitative approach with an explanatory research design. Data were collected through questionnaires distributed to 327 active UNIBA Madura students in the 2023–2024 academic year. The data analysis technique used was Structural Equation Modeling–Partial Least Squares (SEM-PLS) to test the direct and indirect effects between variables. The results of the study indicate that academic service quality and digital access have a positive and significant effect on academic service satisfaction. Furthermore, service quality and digital access also have a positive and significant effect on students' prior experience. The previous experience variable is proven to have a positive and significant effect on academic service satisfaction and is able to indirectly mediate the influence of service quality and digital access on academic service satisfaction. These findings indicate that students' past experiences play a significant role in shaping their perceptions and evaluations of current academic services. Based on the research results, it can be concluded that improving the quality of academic services and strengthening digital access, supported by creating a positive student experience, is a crucial strategy for UNIBA Madura to increase academic service satisfaction. This research is expected to serve as a reference for university administrators in developing academic service policies oriented toward student experience and satisfaction.